SEJARAH APEC DAN TANTANGAN YANG DIHADAPINYA - Atiqah, Atiqah (JOURNAL EQUITABLE, 2017)
APEC is a forum of economic cooperation for countries in the Asia Pacific region, the forum is based on the principle of equality and mutual respect and understanding. In its development, APEC's goals and missions have shifted from economic cooperation to political and security cooperation. This shift is a formidable challenge for APEC member countries in responding to the strong US domination in the APEC forum which has caused disunity among APEC member countries itself, and this is a very relevant opportunity for APEC member countries to return to the original mission.